Phage N4 RNA polymerase II recruitment to DNA by a single-stranded DNA-binding protein - Carter, Richard H. (Cold Spring Harbor Laboratory Press, 2003)
Transcription of bacteriophage N4 middle genes is carried out by a phage-coded, heterodimeric RNA polymerase (N4 RNAPII), which belongs to the family of T7-like RNA polymerases. In contrast to phage T7-RNAP, N4 RNAPII displays no activity on double-stranded templates and low activity on single-stranded templates. In vivo, at least one additional N4-coded protein (p17) is required for N4 middle transcription. We show that N4 ORF2encodes p17 (gp2). Characterization of purified gp2revealed that it is a single-stranded DNA-binding protein that activates N4 RNAPII transcription on single-stranded DNA templates through specific interaction with N4 RNAPII. On the basis of the properties of the proteins involved in N4 RNAPII transcription and of middle promoters, we propose a model for N4 RNAPII promoter recognition, in which gp2plays two roles, stabilization of a single-stranded region at the promoter and recruitment of N4 RNAPII through gp2-N4 RNAPII interactions. Furthermore, we discuss our results in the context of transcription initiation by mitochondrial RNA polymerases.